Possibilities of reading skills improvement via technology: a systematic review - Aboubakr, Fatimah Abdullah Abraheem; Morshed, Farzana; Albaadany, Hanan Yahia Mohammed Ali (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Researchers always have been trying to invent new ways to help teachers and instructors to teach their students the reading skills either using traditional reading skills such as printed texts and books, or by using an assistance technology, such as computers, mobile applications, or software programs. A great number of contributions have been done over past years to investigate the effects of using technology in developing the language acquisition skills in the classroom. This paper follows a systematic approach to review the possibilities of reading skills improvement via technology. The authors discuss the possibilities of making use of different technologies to improve reading skills, not only for English and other languages learners, but also in the case of children who suffer from reading difficulties (dyslexia).